If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -2)(4x + 1) = 0 Reorder the terms: (-2 + 3x)(4x + 1) = 0 Reorder the terms: (-2 + 3x)(1 + 4x) = 0 Multiply (-2 + 3x) * (1 + 4x) (-2(1 + 4x) + 3x * (1 + 4x)) = 0 ((1 * -2 + 4x * -2) + 3x * (1 + 4x)) = 0 ((-2 + -8x) + 3x * (1 + 4x)) = 0 (-2 + -8x + (1 * 3x + 4x * 3x)) = 0 (-2 + -8x + (3x + 12x2)) = 0 Combine like terms: -8x + 3x = -5x (-2 + -5x + 12x2) = 0 Solving -2 + -5x + 12x2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -4x)(2 + -3x) = 0Subproblem 1
Set the factor '(-1 + -4x)' equal to zero and attempt to solve: Simplifying -1 + -4x = 0 Solving -1 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -4x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 0 + 1 -4x = 0 + 1 Combine like terms: 0 + 1 = 1 -4x = 1 Divide each side by '-4'. x = -0.25 Simplifying x = -0.25Subproblem 2
Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667Solution
x = {-0.25, 0.6666666667}
| 145=10x-8 | | 3A+2B=2C | | 3+2*4= | | 7x^2+16x+11=0 | | x^2+9x+22=8 | | 2-4x=3(2-3x) | | 2-4x=3(2-3) | | -2y=-4(0)+5 | | 8y=-4(0)+4 | | 0.008v-32333=72+-22x | | y=1.16(4)+7 | | 5(3X+2)+(X+1)= | | 4(0)+8y=4 | | 6x=1/36 | | y=2(-17.5)+8 | | 0.4x+4=3x-0.7 | | 3(2X+1)+2(X+6)= | | 3x-0.2=4-4x | | 1.2x-6=2x+8 | | 2x^3+4x^2+50=0 | | 8(14)= | | 3xy+9x+y+3= | | x^2-x-41=6x+3 | | 10p^2+9=249 | | -12x+8=-27x+1 | | (v+7)+u= | | 6(5Y+3)+5= | | 3x^2+24x-30=0 | | 5z^2-5z-10=0 | | (3+5A)+5= | | X+6+3X= | | 625x=3125 |